PENGARUH MOTIVASI, PELATIHAN, DAN DISIPLIN KERJA TERHADAP KINERJA - Putri, Belinda Nursabila; Ratnawati, Kusuma (Jurnal Kewirausahaan dan Inovasi, 2023)
This study aims to determine the effect of motivation, training, and work discipline on performance with employee objects on intern employees at PT. Bank Sinarmas Sharia Business Unit (tbk) KCP Malang for the period 2021-2022. This study has a population of 49 interns at PT Bank Sinarmas Sharia Business Unit (tbk) KCP Malang, therefore this study uses saturated samples. The method of this research is to use the type of exploratory research using a quantitative approach. The data collection tool used is a questionnaire and the data used is primary data. Partial least square (PLS) was used to test the hypothesis in this study using SmartPLS 4.0 software. The results showed that motivation and training had a significant effect on performance, while discipline had no significant effect on performance. While simultaneously, it shows that the endogenous variable Performance (Y) can be explained by exogenous variables, namely Motivation (X1), Training (X2), and Discipline (X3) by 57.4%. Therefore, the implication of this research is that the higher the level of motivation and also the training provided, the higher the level of performance of intern employees, while the discipline or lack of discipline of intern employees does not affect the performance of intern employees.